Effect of a calcium hydroxide-based root canal dressing on periapical repair in dogs: a histological study - Leonardo, Mario R.; Hernandez, Maria E. F. T.; Silva, Lea A. B.; Tanomaru-Filho, Mario (Mosby, Inc, 2006)
Objective. To compare the periapical repair of teeth with periapical lesion following root canal treatment by using a calcium hydroxide-based intracanal dressing for several time periods or filling in a single visit.Study design. After induction of periapical lesions in 4 dogs, the root canals were prepared using 5.25% sodium hypochlorite for irrigation, and animals were separated into 4 experimental groups; in group I, root canals were filled in a single session; in groups II, III, and IV, a calcium hydroxide-based dressing was kept in place for 15, 30, or 180 days, respectively. Root canals from groups I, II, and III were filled with gutta-percha cones and AH Plus sealer. After 180 days, animals were killed and histological sections were stained with hematoxylin-eosin to evaluate periapical repair.Results. Periapical repair was better in groups II, III, and IV (intracanal dressing) compared with group I (single session; P <.05).Conclusion. The use of a calcium hydroxide-based intracanal dressing was important for periapical repair in teeth with periapical lesion. Dressing with calcium hydroxide paste results in better periapical repair than when the root canal is filled in a single-session treatment.